Vertical Sealing System on Opaque Ventilated Façade: case study on Brazilian buildings - Blazius, Carina Maccari (2020)
A ventilated façade is a construction system that promotes advantages such as agility in execution, high productivity, time reduction of receiving materials and production, among others. Brazil has no prescriptive normalization about construction of ventilated opaque façades; however, the performance standard (NBR 15.575) could be applied for evaluation of residential buildings. The paper aims to organize information on the ventilated opaque façade construction system contributing to the dissemination of the use of this technology in Brazil. The method adopted in the study was a data survey research of some Brazilian companies that use the ventilated opaque façade system, regarding their location, materials used, type of building (new or retrofit), and type of occupation (residential, commercial, institutional). Results show thermal insulation use is predominant in residence and institutional buildings with ventilated opaque façade, and ceramic is the most used material in Brazil, despite the variety of possible external coating materials. The survey shows that 78% of ventilated opaque façade buildings are non-residential, so there are no norms that could be applied. Finally, more academic works on opaque ventilated façades is necessary in order to help consolidate specific prescriptive norms in Brazil.